Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.5694/j.1326-5377.2005.tb07082.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of occupational violence in Australian urban general practice: a cross‐sectional study of GPs

Abstract: Objective: To establish the prevalence and characteristics of occupational violence in Australian urban general practice, and examine practitioner correlates of violence. Design, setting and participants: Cross‐sectional questionnaire survey mailed to all members (n = 1085) of three urban divisions of general practice in New South Wales in August and September 2004. The three divisions were chosen to provide a range of socioeconomic status (SES) demographics. Main outcome measures: Occupational violence toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 12 publications
6
47
1
3
Order By: Relevance
“…Emergency medicine and psychiatry have been singled out as high risk areas for experiencing work-related violence [32,33]. Reported prevalence of experienced violence among GPs ranges from 21% to 83% depending on methodology and geographical area studied [34-41]. The apprehension about work-related violence has been found to be particularly high in out-of-hours services [31,42-44].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency medicine and psychiatry have been singled out as high risk areas for experiencing work-related violence [32,33]. Reported prevalence of experienced violence among GPs ranges from 21% to 83% depending on methodology and geographical area studied [34-41]. The apprehension about work-related violence has been found to be particularly high in out-of-hours services [31,42-44].…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals in the UK, especially general practitioners (GPs), are consistently at risk of WPV [12], with around 10%–11% of GPs reportedly experiencing assault, 5% threats with a weapon, and 25%–59% verbal abuse [13,14,15]. Additionally, 63.7% of sampled Australian GPs had experienced some violence at work [16]. Research has identified a number of risk factors of WPV.…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified a number of risk factors of WPV. For instance, Magin et al reported that GPs who are female and who have fewer years of experience have a higher likelihood of violence [16]. In addition, nursing is also a high-risk occupation for violent incidents in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, violence not only impacts on the health of victims and perpetrators but also undermines efforts to improve health by increasing outdoor exercise and promoting social cohesion. Moreover, the ability for services to deliver support in communities is eroded by violence against visiting health personnel,11 and even staff in general practices, emergency units and hospital settings are at risk of violence by patients and their relatives 12 13…”
mentioning
confidence: 99%